Novel Diterpenoids from the Twigs of Podocarpus nagi - Yuan-Dong Zheng (Molecules, 2016)
Phytochemical investigation of the twigs of Podocarpus nagi (Podocarpaceae) led to the isolation of two new abietane-type diterpenoids, named 1β,16-dihydroxylambertic acid (1) and 3β,16-dihydroxylambertic acid (2), along with two new ent-pimarane-type diterpenoids, named ent-2β,15,16,18-tetrahydroxypimar-8(14)-ene (3) and ent-15-oxo-2β,16,18-trihydroxypimar-8(14)-ene (4). Their respective structures were elucidated on the basis of spectroscopic analyses, including 1D- and 2D-NMR, IR, CD, and HR-ESI-MS. This is the first time ent-pimarane-type diterpenoids from the genus Podocarpus has been reported. All four new compounds were tested for cytotoxic activity. The MTT assay results showed that compounds 3 and 4 significantly inhibited the proliferation of human cervical cancer Hela cells, human lung cancer A549 cells, and human breast cancer MCF-7 cells at a concentration of 10 μM. Furthermore, using the lipopolysaccharide (LPS)-stimulated RAW264.7 cells, compounds 2 and 4 were found to significantly inhibit nitrogen oxide (NO) production with IC50 values of 26.5 ± 6.1 and 17.1 ± 1.5 μM, respectively.